Detection of common thorax diseases from X-Ray images using a fusion of transfer and statistical learning method - Rafi, Ahmad Abdur; Mahmud, Muhtasim; Pranto, Sakib Dewan; Rahman, Sayemur; Chowdhury, Shihab Rumee (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.